(untitled) (Economic studies journal, 2024)
The study aimed to identify the relationship between obstacles application of electronic management and the employees performance of Emhmed Al-Magarif Hospital at the city of Ajdabiya. The study population consisted of (49) employees , who have administrative responsibilities. The questionnaire was used as a means of collecting data, To analyze data the Statistical Program of Social Sciences (SPSS) was used. The study found that: The level of obstacles to implementing electronic management study was high, The level of employee performance was low, and there is a moderate inverse correlation between organizational obstacles and employees’ performance. It also showed a weak correlation between the obstacles, Technical, human, financial and employee performance, while there was no relationship between human obstacles and employee performance. There are a number of recommendations : the most of which is adopt and apply electronic management, also establishing an administrative unit in the organizational structure that specializes in electronic management. Moreover, The administration allocates a special budget to provide the requirements electronic management application.